2007
DOI: 10.1007/s10669-007-9031-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of aerobically treated distillery sludge mixed with cow dung by using an epigeic earthworm Eisenia fetida

Abstract: The potential of the epigeic earthworm Eisenia fetida to stabilize sludge (generated from a distillation unit of the sugar industry) mixed with cow dung, in different proportions i.e. 20% (T 1 ), 40% (T 2 ), 60% (T 3 ) and 80% (T 4 ) has been studied under laboratory conditions for 90 days. The ready vermicompost was evaluated for its' different physico-chemical parameters using standard methods. At the end of experiment, all vermibeds expressed a significant decrease in pH (7.8-19.2%) organic C (8.5-25.8%) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…N mineralisation is regulated by the availability of DON and NH 4 + , the activity of microorganisms and their relative requirements for C and N (Bardgett, 2005). Accordingly, previous studies have also shown a higher content of total K in the presence of earthworms in vermicomposting trials performed with either sewage sludge or cattle manure (Suthar, 2008;Garg, 2009, 2011). The total K content increased significantly with earthworm activity (F 1,16 = 444.06, P < 0.0001), and its content was dependent on the type of waste (F 1,16 = 15.96, P < 0.01) being up to 2.5 times higher in the cattle manure than in the sewage sludge (Table 2).…”
Section: Resultsmentioning
confidence: 86%
“…N mineralisation is regulated by the availability of DON and NH 4 + , the activity of microorganisms and their relative requirements for C and N (Bardgett, 2005). Accordingly, previous studies have also shown a higher content of total K in the presence of earthworms in vermicomposting trials performed with either sewage sludge or cattle manure (Suthar, 2008;Garg, 2009, 2011). The total K content increased significantly with earthworm activity (F 1,16 = 444.06, P < 0.0001), and its content was dependent on the type of waste (F 1,16 = 15.96, P < 0.01) being up to 2.5 times higher in the cattle manure than in the sewage sludge (Table 2).…”
Section: Resultsmentioning
confidence: 86%
“…When organic matter passes through the gut of earthworm, some phosphorous is converted to a more available form. The release of phosphorous in an available form is performed partly by earthworm gut phosphatase and further release of phosphorus might be attributed to the phosphorus solubilising microorganisms present in worm casts 47. Also, the gut of the earthworm usually produces a considerable amount of alkaline phosphatase, which is an essential enzyme excreted through cast deposition and involved in biogeochemical cycle of phosphorus in soils 48…”
Section: Resultsmentioning
confidence: 99%
“…Haimi and Hutha (1986) have reported that lower pH in vermicomposts might be due to the production of CO 2 and other organic acids by microbial activity during bioconversion of wastes substrates. Suthar (2008) has reported that the shift in pH could be due to microbial decomposition during the process of vermicomposting. Elvira et al (1998) have concluded that production of CO 2 and organic acids by microbial decomposition during vermicomposting lowers the pH of substrate.…”
Section: Physico-chemical Changes In Wastes During Vermicompostingmentioning
confidence: 99%
“…Earthworm biomass production and reproduction performance was excellent in bedding which contained lower proportions of distillery sludge (20-40%). Suthar (2008) also reported the vermicomposting of aerobically treated distillery sludge mixed with cow dung in different proportions (20-80%) under laboratory conditions using Eisenia fetida. At the end of experiment, final product produced from all vermibeds showed a decrease in pH (7.8-19.2%), organic C (8.5-25.8%) content, and an increase in total N (130.4-170.7%), available P (22.2-120.8%), exchangeable K (104.9-159.5%), exchangeable Ca (49.1-118.1%), and exchangeable Mg (13.6-51.2%) content (Table 3).…”
Section: Distillery Industry Wastementioning
confidence: 99%